THE EFFECT OF CUTTING SPEED ON CUTTING QUALITY WITH LASER CUTTING MACHINE - Yusuf, Arya (Transpublika Publisher, 2024)
This research investigates the influence of cutting parameters on a laser cutting machine when used on acrylic material. The primary objective of this study is to analyze how cutting speed, electric current, and the type of material affect the quality of the cutting results. An experimental method was employed by varying the cutting speed and adjusting the electric current during the process, followed by measuring the width and precision of the cuts produced. The findings indicate that as cutting speed increases, the width of the cut decreases, resulting in a finer cut. Additionally, higher electric currents can enhance the precision of the cut, ensuring more accurate results. Furthermore, materials with lower melting points were found to be easier to cut with less effort. These results emphasize that the correct combination of cutting parameters is crucial in achieving optimal cutting performance and improving productivity. This study concludes that careful calibration of cutting speed, current, and material selection is essential for obtaining high-quality laser cutting outcomes and enhancing manufacturing efficiency.